2005
DOI: 10.1111/j.1399-5618.2004.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in bipolar disorder: age of onset, course, comorbidity, and symptom presentation

Abstract: Men and women were generally similar in their symptom presentation, age of onset of bipolar disorder, and in the total number of mood episodes. However, they differed in the type of episode at onset and comorbidity patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
116
3
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(144 citation statements)
references
References 44 publications
(60 reference statements)
17
116
3
6
Order By: Relevance
“…Previous research has indicated that eating disorders are significantly more common among female bipolar patients as compared to males (27), a finding that is consistent with prevalence estimates from epidemiologic studies (28,29). One explanation for our discrepant results concerns the elevated rate of threshold and subthreshold BED in the present sample relative to rates of AN or BN.…”
Section: Discussioncontrasting
confidence: 34%
“…Previous research has indicated that eating disorders are significantly more common among female bipolar patients as compared to males (27), a finding that is consistent with prevalence estimates from epidemiologic studies (28,29). One explanation for our discrepant results concerns the elevated rate of threshold and subthreshold BED in the present sample relative to rates of AN or BN.…”
Section: Discussioncontrasting
confidence: 34%
“…Impaired appetite is one of the common features of depressed or bipolar individuals (Diagnostic and Statistical Manual IV 1994, Sugahara et al 2004, Kawa et al 2005, Kishi & Elmquist 2005. However, a reduced appetite is observed in most depressive patients, while an increase in appetite is seen in fewer patients (Diagnostic and Statistical Manual IV 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both disorders display alterations in gating and psychomotor functions (Braff and Geyer, 1990) and are predominantly present in male subjects. For example, androgens have been shown to induce manic symptoms (Pope et al, 2000;Weiss et al, 1999), and the frequency of manic episodes is higher in bipolar male patients than in their female counterparts (Hendrick et al, 2000;Kawa et al, 2005). Similarly, TS incidence in men is four times higher than that in women (Pauls et al, 1990), and anabolic androgens exacerbate TS symptoms (Leckman and Scahill, 1990).…”
Section: -A-reductase Inhibitors In Models Of Psychosis M Bortolato mentioning
confidence: 99%